2011
DOI: 10.4236/jemaa.2011.35027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Power Microwave Fields on Seed Germination and Growth Rate

Abstract: Experiments were conducted to investigate the effects of low power microwave radiation on germination and growth rate in seeds. In the present paper, the bioeffects of low power (non-thermal intensity) microwave modulated with 1 KHz square wave have been studied. Experiments were performed in X-band frequencies using klystron based microwave test bench. Microwave parameters like frequency, power, exposure time and power density were varied while irradiating seed samples to study their influence on germination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…The GR of tartary buckwheat seeds signifi cantly increased (P<0.05) as the microwave power increased but was signifi cantly reduced when the exposure time was increased from 10 s to 30 s at higher irradiation power (>600 W) ( Figure 1). These results were in accordance with previous studies in wheat [Ragha et al, 2011;Gaurilcikiene et al, 2013]. When the exposure time was extended, there was an improvement in the activities of the enzymes in the seedlings.…”
Section: Discussionsupporting
confidence: 93%
“…The GR of tartary buckwheat seeds signifi cantly increased (P<0.05) as the microwave power increased but was signifi cantly reduced when the exposure time was increased from 10 s to 30 s at higher irradiation power (>600 W) ( Figure 1). These results were in accordance with previous studies in wheat [Ragha et al, 2011;Gaurilcikiene et al, 2013]. When the exposure time was extended, there was an improvement in the activities of the enzymes in the seedlings.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, exposure of corn (Zea mays) grains to microwaves resulted in improved grain germination, leaves with greater midrib vascular bundle length, thicker mesophyll, faster growth rate, higher contents of photosynthetic pigments, total soluble sugar and total carbohydrates (Khalafallah and Sallam, 2009). In fact, it has been suggested that low to moderate power and exposure time of microwave radiation stimulate the germination and seedling vigor of plants, while irradiation with increased frequency and power density reduce the seed germination and seedling vigor (Ragha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In case of wheat, green gram and bengal gram, decrease in trend was observed for vegetative growth and chemical constituents observed with increase in exposure time as compare to control (Ragha et al, 2011).…”
Section: Protein Analysis (Sds-page) In Acacia Farnesianamentioning
confidence: 77%